Pengaruh Pendapatan Dan Biaya Terhadap Sisa Hasil Usaha Pada Koperasi Karyawan PT DNP Indonesia “Wira Bhakti” Kawasan Industri Pulogadung Jakarta - Devia Ramadhani , Devia Ramadhani (Cakrawala Akuntansi & Manajemen, 2024)
This study aims to examine the effect of income and costs on the remaining results of operations at the PT.DNP Indonesia "Wira Bhakti" Employee Cooperative for the 2016- 2022 period and to test how significant the effect of the income and cost relationship is on the remaining operating results at the PT.DNP Indonesia Employee Cooperative "Wira Bhakti” for the 2016-2022 period. This study uses a quantitative approach with primary and secondary data. Primary data collection was obtained through interviews and documentation of the cooperative's financial reports, while the secondary data contained literature on information on income, costs and remaining business results of PT. DNP Indonesia "Wira Bhakti" Employee Cooperative for the 2016-2022 period. The sampling technique uses purposive sampling. Data analysis techniques used descriptive statistical tests, classical assumption tests (normality, heteroscedasticity, multicollinearity, autocorrelation), multiple linear regression, T-test, F-test and the coefficient of determination. The statistical tool used was SPSS Version 25. The results of this study indicated that the data were normally distributed and there were no problems with heteroscedasticity, multicollinearity and autocorrelation. Based on the results of the T test showed that partially, income has a significant positive effect on the remaining results of operations, and costs have a significant positive effect on the remaining results of operations (H1 and H2 are accepted). And the results of the F test, simultaneously there is a significant influencebetween income and costs on the remaining results of cooperative operations (H3 is accepted). Thus, this study concludes that income and costs have an influence on the remaining results of operations at PT. DNP Indonesia "Wira Bhakti" Employee Cooperative. These results have practical implications for companies in managing their finances and business strategi